From the Editors - Zinkow, Leszek (Perspektywy Kultury, 2022)
An examination of the meanders of how the heritage of antiquity is received in contemporaneity is usually associated with the legacy of Greek and Roman culture. In the current issue, we propose a slightly different perspective – on the interesting and intriguing themes drawing from the achievements of cultures of the ancient East, primarily Egypt. This thread appears in the articles of the theme section of this issue of Perspectives on Culture.